Digital Divide and Poverty Eradication in the Rural Region of Northern Peninsular Malaysia - Sharifah Rohayah Dawood (Indonesian Journal of Geography, 2019)
One of the ways to eliminate poverty is through Information and Communication Technologies (ICTs) that is often promoted as central to reviving and sustaining regional communities. In the context of Malaysia, however, the level of communication in urban and rural areas has seen a gap in terms of access to ICTs. Though various initiatives are taken to close the digital gaps, more efforts are needed. This paper intends to explore the extent to which ICTs in rural areas of northern Peninsular Malaysia are able to raise the socio-economic development of the communities. Using questionnaires and in-depth interviews, emphasis is given to analyze the role of ICTs in poverty reduction processes upholding regional developments. It has been observed that solving common causes for the communities’ access and socio-economic growth needs strategic implementation of policies at the central core and pragmatic implementation of actions at the grass root level.